Tafsir Tematik: Konsep Manajemen Perspektif Ayat-Ayat Al-Qur’an - Sutrisno, Andri; Fajriyah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
In essence management serves to carry out all activities that need to be carried out in order to achieve the best goals in an organization. Thus, to achieve a good goal, it must be in accordance with the guidance of Islam. Where the Qur'an becomes a guide in this life. So that the concept of management in the verses of the Qur'an can achieve a goal that is desired by the organization. The research uses a descriptive qualitative approach to the type of library research in which researchers examine and analyze the interpretation of Qur'anic verses related to the concept of management. So it can be concluded that the concept of management in the verses of the Qur'an has two meanings namely At-Tadbir (arrangement) and Ar-Rabbu (ruler).